(untitled) (International journal of medical sciences, 2026)
Subclinical hypothyroidism (SCH) is a common endocrine disorder characterized by elevated serum thyroid-stimulating hormone (TSH) levels with normal circulating free thyroxine (fT4) concentrations. Despite its high prevalence, particularly among women and the elderly, the management of SCH remains controversial. While some patients progress to overt hypothyroidism or develop cardiovascular and metabolic complications, others remain stable or even revert to euthyroidism without intervention. Recent studies have produced conflicting results regarding the benefits of levothyroxine therapy, especially in mild forms of the disease. This review aims to summarize current knowledge on the epidemiology, pathophysiology, clinical implications, diagnostic approach, and treatment strategies of subclinical hypothyroidism, with a particular focus on identifying patients who may benefit from pharmacological intervention.